Chlorination Of Nitrided Malaysian Ilmenite Concentrate Reduced With Polypropylene And Coal - Ibrahim, Najwa (2019)
The production of Titanium Oxycarbonitride (TiOxCyNz) from Malaysian ilmenite and its chlorination at low temperatures for production of Titanium Tetrachloride (TiCl4) was studied in this project. The objective was to improve an alternative technology for production of TiCl4. The effects of carbothermal reduction and nitridation (CTRN) on parameters of time, carbon to oxygen molar ratio (C:Ored) and the addition of waste PP plastic into coal (PP:MB coal) on the formation of Fe and TiOxCyNz from ilmenite were investigated. Design of Experiments (DOE) was assigned to design the parameters in CTRN process. The CTRN process was done at temperature of 1150 and 1250 °C under H2-N2 atmosphere for 60 and 180 min. A mixture of C:Ored molar ratio ranging from 3.0 and 7.0 ratios. The extent of reduction (XO) and the extent of nitridation (XN) was increasing as increase PP:MB coal content from 25 wt. %, 60 wt. % and 100 wt. %. SEM/EDX analyses showed that the product synthesized by 60 wt. % and 100 wt. % PP had a unique microstructure in which is spherical Fe particles. This spherical Fe can be easily separated from TiOxCyNz phase. The highest XO and XN were 93.15% and 93.85%; respectively for C7PP1004. After CTRN process, Fe removal was carried out for 8 hours by an aeration leaching Becher type process at 70 °C in the presence of NH4Cl and 0.1 wt. % AQ-2 as the effective catalysts. Again DOE was used in chlorination to design the experiment run. The parameters for chlorination were time (30 min and 60 min),temperature (300 °C and 400 °C) and N2 gas flowrate (200 mL/min and 400 mL/min). The XTi moderately increased with increasing the temperature and decreasing flow rate of N2 gas from 200 mL/ min to 400 mL/min. The highest weight loss and XTi of TiOxCyNz at 300 °C and 400 °C were 84.0% and 88.7 % in 60 minutes, respectively. The TiCl4 with the purity of about 97% was eventually produced from Malaysian ilmenite. Therefore, project demonstrated that the process of CTRN, leaching process and chlorination process could be a feasible method in production of TiCl4.